Sweden — a model of consensus and rationality? New directions in regional planning in the stockholm region - Böhme, Kai (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Regional planning in Sweden is neither institutionalised in a manner comparable to the situation found in Germany, nor can it look back on a similarly long tradition. One reason for this is to be found in the near unassailable planning monopoly of local authorities. This case-study of regional planning in Stockholm shows that neither corporate pluralism nor the central importance attached to rational, consensus-based planning is being seriously called into question. What disharmony does exist is over the relationship between planning and politics. Although planning is informal and only vaguely defined, it is still important to ask whether there is anything for regional planning in Germany to learn from Sweden. Could Sweden provide a model?